2020
DOI: 10.1037/tmb0000008
|View full text |Cite
|
Sign up to set email alerts
|

Cybersex with human- and machine-cued partners: Gratifications, shortcomings, and tensions.

Abstract: From social-network spambots and forensic chatbots to dating simulation games, sexual communication with machines is not uncommon in contemporary culture-however, it remains effectively a black-box phenomenon. There is little empirical research examining how sexual human-machine communication (HMC-S) is experienced, whether it is impactful, or whether it may be similar or different to human-human sexual communication. Advancing our understanding of those questions is vital in understanding the potential for ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 64 publications
(82 reference statements)
1
6
0
Order By: Relevance
“…In the realm of the SIIM and in accordance with results of an empirical study by Banks and van Ouytsel (2020), the results (especially in terms of attractiveness and flirtatiousness) indicate that the voice assistant achieved no goodness-of-artificial fit, which might be due to constraints such as social and sexual norms (intimate or sexualized interactions are preserved for humans) but also evolutionarily rooted aversions (artificial humans may provide cues that deviate from healthy humans, e.g., voice, which might automatically trigger aversion). As the SIIM is based on the media equation theory, it also needs further research on whether it can be applied in the context of digitalized sexuality.…”
Section: Effects Of the Communication Partner's Ontological Class (H1...supporting
confidence: 87%
See 3 more Smart Citations
“…In the realm of the SIIM and in accordance with results of an empirical study by Banks and van Ouytsel (2020), the results (especially in terms of attractiveness and flirtatiousness) indicate that the voice assistant achieved no goodness-of-artificial fit, which might be due to constraints such as social and sexual norms (intimate or sexualized interactions are preserved for humans) but also evolutionarily rooted aversions (artificial humans may provide cues that deviate from healthy humans, e.g., voice, which might automatically trigger aversion). As the SIIM is based on the media equation theory, it also needs further research on whether it can be applied in the context of digitalized sexuality.…”
Section: Effects Of the Communication Partner's Ontological Class (H1...supporting
confidence: 87%
“…While no concrete research has yet been conducted on how voice assistants are perceived in this context compared to humans, Banks and van Ouytsel (2020) conducted an empirical study on how people interacted with a sexualized chatbot that either displayed human or machine-like cues (e.g., extended typing delays or visual and textual indicators of sex). While manipulation checks indicated that most of the respondents were aware that the chatbot showing human-like cues, was also a bot instead of a human, results also showed that the participants experienced sexual arousal across both conditions.…”
Section: Theoretical Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The third subtype focuses on sexual interactions with software sexbots (e.g., AI-enabled chatbots; Banks and van Ouytsel, 2020 ; AI-enabled holograms; Liu, 2021 ). Those software artifacts are not tangible but invite the user to engage in social, romantic and sexual interactions and relationships.…”
Section: Sexual Interaction With Digital Technologiesmentioning
confidence: 99%